Facilitation of visuo-motor learning by transcranial direct current stimulation of the motor and extrastriate visual areas in humans - Antal, Andrea; Nitsche, Michael A.; Kincses, Tamás Z.; Kruse, Wolfgang; Hoffmann, Klaus-Peter; Paulus, Walter (The European journal of neuroscience, 2004)
Performance of visuo‐motor tasks requires the transfer of visual data to motor performance and depends highly on visual perception and cognitive processing, mainly during the learning phase. The primary aim of this study was to determine if the human middle temporal (MT)+/V5, an extrastriate visual area that is known to mediate motion processing, and the primary motor cortex are involved in learning of visuo‐motor coordination tasks. To pursue this, we increased or decreased MT+/V5, primary contralateral motor (M1) and primary visual cortex excitability by 10 min of anodal or cathodal transcranial direct current stimulation in healthy human subjects during the learning phase of a visually guided tracking task. The percentage of correct tracking movements increased significantly in the early learning phase during anodal stimulation, but only when the left V5 or M1 was stimulated. Cathodal stimulation had no significant effect. Also, stimulation of the primary visual cortex was not effective for this kind of task. Our data suggest that the areas V5 and M1 are involved in the early phase of learning of visuo‐motor coordination.